Coarse-Grained Simulation Of Calbindin D9k - Thapa, Mahendra; Rance, Mark (Scientific World, 2021)
The coarse-grained protein modeling tool, Cabs-flex, is feely available online server; it is based on the CABS model in which each residue of a protein has been represented by four points. The server was used for the protein Calbindin D9k in it’s doubly calcium loaded state: small and single domain protein of the EF-hand family. Twelve representative structures, in all-atom format corresponding to each cluster, were also downloaded along with trajectories, ready-made plots, images, video, data files of Cα RMSD, atomic fluctuation and GDT_TS. In the present study, simulated Cα atomic fluctuations for residues of the protein was compared with the experimental results and also correlated with the respective Cα RMSD and GDT_TS.